Merjenje geografske razširjenosti ptic - Janžekovič, Franc (Acrocephalus, 2000)
The author presents six methods for estimating the geographical distribution of birds. The estimates were made on 216 species, all of them probable or confirmed Slovene breeders. Three approaches to the distribution estimates were compared: (1) distance between the most distant nest-sites; (2) surface area of the inhabited territory, (3) the habita's specific features. It was concluded that the results between different methods were more or less related, but that the methods were not fully comparable (equivalent). The distances between the most distant nest-sites, which are measured parallel with latitude and longitude, are not suitable for the surface area covered by Slovene territory. With them, distributions in large areas are usually measured. Estimates of the surface area of inhabited areas or presentations of species' distribution with squares are only approximate and in some cases misleading. Nests or nest-sites, which are in fact points, are usually extrapolated on the 10 x 10 km squares (=100 km2). This is why an accurate geolocation of concrete data must be assured in the preparations for the new mapping of birds
Keywords: bird; ptice; ornitologija; geografska razširjenost; gnezdenje; Slovenia; Slovenija